The Devil's in the Detail: A review of Group I and III Petrographic Thin-Sections - Mik Markham (Internet Archaeology, 2009)
Re-examination of 149 IPG Group I (119), Group Ia (17) and Groups III and IIa (13) axe petrographic thin-sections in a short period of time resulted in 24 sub-groups being identified, each sharing distinct petrographic features. Approximately 5% (8 thin-sections) had distinctive mineralogy, different from that of altered dolerite (greenstone), which defines these IPG Groups. All 149 thin-sections are visually compared with 73 new petrological thin-sections that were produced from 13 greenstone exposures in North and South Cornwall. The closest petrological match between axe and greenstone suggests Mounts Bay, possibly Long Rock. Mousehole and Penlee exposures may be the source of material for some of the 24 sub-groups. Two greenstone samples found in north-west Cornwall, away from known exposures, provided the closest petrographic match found between axe and rock thin-sections. This supports Keiller et al. (1941) in their assumption that IPG Group I originates from Mounts Bay, but indicates it is unlikely that a single exposure provided the material for all IPG Group I axes. Further analysis using a novel quantitative technique supports the results of the visual examination and may prove to be the basis of a future tool to be used in recording and assigning Neolithic axes to IPG Groups.